Sistem Pendukung Keputusan Pemilihan DC (Distribution Center) Terbaik Setiap Bulannya Pada DC Indomaret Secara Nasional Menggunakan Metode Fuzzy-AHP Dan SMARTER - Nurhidayah, Ummi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Decision Support System (DSS) is a part of computer-based information systems, including knowledge-based systems or knowledge management used to support decision-making in an organization or company. Decision support systems can be developed using various methods, two of which are Fuzzy-AHP and SMARTER methods. A Distribution Center (DC) is a hub for controlling and distributing goods, such as those of Indomaret, where goods are stored and processed for even distribution to each store. The best DC is a recognition given to a center with the best performance. The selection of the best DC nationally every month is a routine activity carried out by PT. Indomarco to appreciate DC performance. The Fuzzy Analytical Hierarchy Process (F-AHP) method utilizes fuzzy ratios called Triangular Fuzzy Numbers (TFN) and is used in the fuzzification process. TFN consists of three membership functions: the lowest value (l), the middle value (m), and the highest value (u). Meanwhile, the SMARTER method (Simple Multi-Attribute Rating Technique Exploiting Rank) is one of the methods for implementing Decision Support Systems. It involves determining criteria and sub-criteria along with their weights using ROC (Rank Order Centroid). The final result is the utility value of each criterion, leading to the ranking of each alternative.